How valid is a skin health questionnaire for occupational skin surveillance?. (19th October 2011) - Steiner, Markus; Dick, Finlay; Semple, Sean; Ormerod, Anthony; Murphy, Elizabeth; Ayres, Jon
Abstract : Objectives: As part of a study evaluating the diagnostic accuracy of a teledermatologic tool for occupational skin surveillance we tested the validity of the standard UK Health and Safety Executive (HSE) skin health questionnaire against visual inspection by a trained occupational physician. Current self-reported symptoms were compared with the assessment by the physician carried out at the same time. Methods: Data were collected from 332 participants in four occupational groups (healthcare workers, hairdressers, engineering workers and nursery nurses) seen on one to seven occasions over a 7 month period. Overall 1212 sessions with valid questionnaire and visual inspection were gathered. Self-reported symptoms were compared against 'Dry skin' (minor dermatitis) and 'Dermatitis' from the visual inspection. Results: With visual inspection as diagnostic standard and a 37% point prevalence of hand dermatitis/dry skin at baseline (332) the HSE questionnaire showed a specificity of 82% (95% CI: 77 to 87%) and a sensitivity of 53% (95% CI: 44 to 62%). The positive and negative predictive values were 64% (95% CI: 54 to 73%) and 75% (95% CI: 69 to 81%) respectively and the κ showed a fair agreement at 0.37 (95% CI: 0.26 to 0.47). Applied to the total sample the results changed slightly with an increased positive predictive value (74%) and decreased sensitivity (49%). Conclusions: Our results show that the recommended questionnaire only identified two-thirds of workers with visible skin problems. The failure of the current HSE skin health questionnaire to recognise a large proportion of workers with skin disease may have important consequences in terms of early intervention and progression of dermatitis to more serious and disabling forms.